(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
The purpose of the study was to identify the factors in the application of blockchain technology in the food supply chain based on a bibliometric review of academic and professional papers obtained from the indexed database Scopus using analysis tools to visualize and build bibliometric networks. The results allowed identifying traceability, internet of things and trust as factors that influence the application of blockchain technology in the food supply chain ensuring competitiveness and sustainable development in medium, small and large companies. In addition, 50% of the analyzed articles on Blockchain in the food sector focus on the regions of India, China, Italy and the United Kingdom. Recommending the application of this technology in non-traditional agricultural products due to its reliability.